THE PROSPECTS OF SPECIAL REGULATION FOR ONLINE DISPUTE RESOLUTION (ODR) TO PROTECT ONLINE CONSUMER IN INDONESIA - Muhammad Daffa Fadlilnaufal; Muh. Afif Mahfud; Pulung Widhi Hari Hananto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2026)
Indonesia is the largest e-commerce market in Southeast Asia with 229.4 million internet users and digital transaction values reaching IDR 487 trillion per year. The surge in digital consumer disputes characterized by low value, high volume, and cross-jurisdictional nature reveals a fundamental mismatch with conventional dispute resolution mechanisms such as BPSK and small claims courts, further compounded by a 73% budget cut to the BPKN in 2025. This research analyzes the urgency and ideal architecture of a lex specialis Online Dispute Resolution (ODR) regulation within Indonesia's legal system, through a comparative study with the European Union model and UNCITRAL international standards. A normative-doctrinal legal method is employed with legislative, conceptual, and comparative approaches. Results demonstrate a paradigmatic failure of existing legal frameworks designed for physical-local disputes and the necessity of selectively adopting the EU model with mandatory compliance modifications integrated with national digital identity infrastructure.